2023
DOI: 10.3389/fnut.2022.1042719
|View full text |Cite
|
Sign up to set email alerts
|

Almond intake alters the acute plasma dihydroxy-octadecenoic acid (DiHOME) response to eccentric exercise

Abstract: IntroductionThis investigation determined if 4-weeks ingestion of nutrient-dense almonds mitigated post-exercise inflammation and muscle soreness and damage.MethodsAn acute 90-min of eccentric exercise (90-EE) was used to induce muscle damage in 64 non-obese adults not engaging in regular resistance training (ages 30–65 years, BMI < 30 kg/m2). Using a parallel group design, participants were randomized to almond (AL) (57 g/d) or cereal bar (CB) (calorie matched) treatment groups for a 4-week period prio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(33 citation statements)
references
References 56 publications
5
27
0
Order By: Relevance
“…During recovery from 75-km cycling in trained endurance athletes, for example, blueberry intake mitigated exercise-induced increases in pro-inflammatory oxylipins but did not elevate anti-inflammatory omega 3-generated oxylipins [22]. In a similar design to the current study, we recently reported that 4weeks intake of 57 g/d almonds was related to a significant post-exercise increase in 12,13-diHOME and a decrease in 9,10-diHOME, with no significant effects on other oxylipins [23]. This disparate diHOME response to eccentric-based exercise may have in part been related to the unique nutrient and polyphenol profile of almonds [23].…”
Section: Discussionsupporting
confidence: 57%
See 4 more Smart Citations
“…During recovery from 75-km cycling in trained endurance athletes, for example, blueberry intake mitigated exercise-induced increases in pro-inflammatory oxylipins but did not elevate anti-inflammatory omega 3-generated oxylipins [22]. In a similar design to the current study, we recently reported that 4weeks intake of 57 g/d almonds was related to a significant post-exercise increase in 12,13-diHOME and a decrease in 9,10-diHOME, with no significant effects on other oxylipins [23]. This disparate diHOME response to eccentric-based exercise may have in part been related to the unique nutrient and polyphenol profile of almonds [23].…”
Section: Discussionsupporting
confidence: 57%
“…Relatively few acute and chronic exercise-based studies have been conducted using oxylipins as a primary outcome measure [5,[15][16][17][18][19][20][21][22][23][24]. In general, the acute post-exercise increase in plasma levels of oxylipins is more diverse and greater with prolonged and intensive cardiorespiratory exercise (e.g., 2-3 h of cycling and running) than with resistance-based exercise bouts [5,[16][17][18][22][23][24]. After 2-3 h of intensive cycling or running, plasma oxylipins peak between 0-and 1.5 h post-exercise and then fall to near-pre-exercise levels by 5 h post-exercise [22].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations